2020
DOI: 10.3389/fpsyg.2019.02961
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Maltreatment Experience Influences Neural Response to Psychosocial Stress in Adults: An fMRI Study

Abstract: Background: Childhood maltreatment is a strong risk factor for the development of depression in later life. However, the neurobiological mechanisms underlying this vulnerability are not well understood. As depression has been associated with dysfunction of the hypothalamic-pituitary-adrenal (HPA) axis and increased responsiveness to psychosocial stressors, we speculated that childhood maltreatment may lead to lasting alteration of the stress response system, thereby increasing the risk of depression. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 59 publications
2
19
1
Order By: Relevance
“…Interestingly, other studies have also reported structural reductions in the occipital cortex among maltreated children ( McLaughlin et al, 2014 ) and adults with a history of childhood abuse ( Tomoda et al, 2009 ). Further, these structural findings are in line with results from functional-based MRI studies Specifically, studies have shown that adults with and without a history of childhood maltreatment evidence divergent activation patterns in both the prefrontal and occipital cortices ( Frewen et al, 2017 , Seghete et al, 2017 , Zhong et al, 2020 ). Thus, the findings of the present study fit within the greater neuroimaging literature documenting links between childhood adversity and neural adaptations within these cortices.…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, other studies have also reported structural reductions in the occipital cortex among maltreated children ( McLaughlin et al, 2014 ) and adults with a history of childhood abuse ( Tomoda et al, 2009 ). Further, these structural findings are in line with results from functional-based MRI studies Specifically, studies have shown that adults with and without a history of childhood maltreatment evidence divergent activation patterns in both the prefrontal and occipital cortices ( Frewen et al, 2017 , Seghete et al, 2017 , Zhong et al, 2020 ). Thus, the findings of the present study fit within the greater neuroimaging literature documenting links between childhood adversity and neural adaptations within these cortices.…”
Section: Discussionsupporting
confidence: 86%
“…It is reasonable that emotional abuse is a risk factor of depression and anxiety symptoms, while resilience and good parent-child relationship are protective factors with moderating effects in adolescents during the outbreak of COIVD-19. Moreover, we appeal to stop emotional abuse as well, for childhood maltreatment can negatively influence mental health of adolescents, it has been proved by previous studies ( Geoffroy et al., 2016 ; ten Have et al., 2019 ; Zhong et al., 2020 ).…”
Section: Discussionmentioning
confidence: 96%
“…However, the mechanism for this relationship is unclear. It could be linked to post-traumatic changes in brain function or HPA axis responsiveness to stress ( 37 ). Based on the findings described above, interventions to address somatic complaints in male adolescents with hyperactivity symptoms should consider the effects of trauma and life events alone, and the interaction between childhood traumatic experiences and life events should be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Zhong et al found that childhood trauma changed brain function (dorsolateral pre-frontal cortex, insula, etc.) and hypothalamic-pituitary-adrenal (HPA) axis responsiveness to stress ( 37 ). Recently, Janiri et al reported that childhood trauma increased vulnerability to stress-related psychological distress during the coronavirus disease 2019 outbreak ( 38 ).…”
Section: Introductionmentioning
confidence: 99%